Willingness to eat an insect based product and impact on brand equity: A global perspective - Castro, Mauricio; Chambers, Edgar, IV (My University, 2019)
Rapid population growth is creating the need to find new and sustainable food sources. Insect-based products could satisfy this high priority necessity while incorporating important nutrients in the human diet such as protein, vitamins, and minerals. This research provides a global overview of the willingness to try a new product that contains insect powder and determine the impact of adding insect-based products to a brands portfolio. An international survey was conducted in 13 different countries (n = 630 consumers per country, total 7,800 consumer) with consumers who represented diverse demographic backgrounds. Eight of the 13 countries could be classified as “disgust” countries where most respondents said they would not be willing to try a familiar product containing insect powder. Nine countries fell into the “impact” category where participants would be more likely to stop buying other products from this company knowing that they have used insect powder in another product from the same brand. The reasons why participants would not consider eating foods containing insect powder were religion, the perception that insects carry diseases and cause allergic reactions. Only the disease-carrying perception was significant in most of the countries. Practical applications The results from this study showed that most consumers from most countries studied are not willing to try insect-based products at this time. However, there was a segment of the population in each country that was willing to try such products. There is a great opportunity for companies to create new products for countries where the disgust factor was not a barrier and to test those new concepts and products. This could help provide information to educate consumers about all the benefits of insect protein and implement. It is key to remember that new brands probably are necessary for such products because of the potential damage to brand equity of introducing products containing insect powder.
Citation: Castro, M., & Chambers, E. (2019). Willingness to eat an insect based product and impact on brand equity: A global perspective. Journal of Sensory Studies, 34(2), e12486. https://doi.org/10.1111/joss.12486